QUALITY OF PUBLIC OPEN SPACE BASED ON VISITORS PERCEPTIONS AND EXPECTATIONS. CASE STUDY: MAHAKAM RIVERSIDE IN TENGGARONG CITY - Nur Asriatul Kholifah; Citra Anggita; Ikhwanul Ahfadz; Hani Frisca (Universitas Pendidikan Indonesia, 2022)
Public open space is one part of urban space that functions to improve environmental quality, city aesthetics, and social interaction. Tenggarong city in East Kalimantan Province, which is located on the banks of the Mahakam River, has public open spaces along its riverbanks. The beginning of the concept of developing this riverside area is The Waterfront Park of Tenggarong City or tourism on the Mahakam Riverside. This public open space aims to restore the function of city space and places that have a linear typology, as well as a city icon and increase tourist visits to Tenggarong City. The purpose of this research is to find out how the quality of public open space is viewed from the perceptions and expectations of visitors and to find out the factors that influence the expectations of visitors to the Mahakam Riverside in Tenggarong City. This study refers to the theory of the quality of public open space which includes meaningful, responsibility, democratic, and maintenance. The result of this research is in